Time management - Williams, Kate (Palgrave Macmillan, 2015)
This easy-to-use guide helps students to improve their time management skills. Focusing specifically on challenges posed within a higher education context, it provides practical advice for students at all levels. Concise yet effective, the book's informal style is supplemented by engaging illustrations.